“SEGIZ QYRLY, BIP SYRLY”: NATIONAL FACE OF PERSON IN KAZAKH CULTURE (BASED ON MUSICAL AND ARTISTIC-CRAFT) - Khazbulatov, Andrei; Шайгозова, Жанерке; Mombek, Aliya (Pedagogy and Psychology, 2022)
Traditional ideas about the perfect man are an important part of the immaterial cultural heritage, shown in various folk oral and poetic forms: fairy tales, proverbs, sayings, idioms, etc. One of this idioms is “Segiz qyrly, bir syrly”, which means “Eight facets - one integral essence”, used as the title of this article is known to almost every Kazakh. The national memory preserves many names, who were honored with these words. Now they sound not often, but more straight and sharper. The authors of this article are trying to open these “eight facets, and one integral essence” – the Turkic ideal of the perfect man, based on the Kazakhs, who formed and “recrystallized” throughout thousands of years. This ideal contains the entire cultural and historical experience of the ethnos, which passed down from one generation to another from ancient times until ethnographic modernity. Of course, the perfect identity has an universal character. Every nation has its own. The Chuvash has “seven blessings” or the observance of the “seven commandment”, among the Buryats, it is the “nine virtues” of a person, etc. In this article, the authors focused on one of such specifications of ethnic ideas about a perfect identity, expressed in Kazakh culture through the concept of an “octahedral” person. The authors are sure that based on this materials they can show deeper knowledge for teachers, researchers and students od pedagogical institutions, who use national pedagogy and non-material heritage. “octahedron” through the prism of the musical and artistic-craft spheres which, more than all the components of culture, demonstrates the various aspects of this phenomenon. The reconstruction of the meaning/sense of the analyzed idiom showed that the number “8” is primarily a symbol of human cognition/achievement of the essence of Tengrian spiritual teaching together with sacred knowledge. The authors are ensuring that the materials obtained will help to expand and deepen the knowledge of teachers, researchers and students of pedagogical universities practicing in the studies concerned on folk pedagogy and immaterial cultural heritage. The article was prepared within the project of the Ministry of Education and Science of the Republic of Kazakhstan AR09259280 “Languages of Kazakh culture as the basis of ethnic identity: semiotics and semantics”.